THE EFFECT OF CIRC STRATEGY AND ACHIEVEMENT MOTIVATION TOWARD STUDENTS’ READING COMPREHENSION - Rahmawati, L. Rahmawati (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2018)
The aim of this study is to investigate (1) whether there is a difference in the reading comprehension between students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) an interactional effect between the reading strategy applied and achievement motivation toward students? reading comprehension; (3) a difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy; and (4) a difference in reading comprehension between students with low achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy. The study administrated a 2X2 factorial design, which 175 students were involved as the sample. The data were collected by using questionnaire and a reading test then analyzed by Two-way ANOVA. The result indicates that (1) there is a significant difference in reading comprehension between the students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) there is an effect of the interaction between the teaching strategy applied and students? achievement motivation toward their reading comprehension; (3) there is a significant difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy; and (4) there was significant difference in reading comprehension between the students with low achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy.